How wear, age, and sex relate to enamel chipping in Cayo Santiago rhesus macaques (Macaca mulatta) - Debbie Guatelli-Steinberg; Luke D. Fannin; Qian Wang (PLoS ONE, 2025)
In living primates, bite forces required to fracture hard-object foods can result in high frequencies of chipped teeth, providing a comparative basis for inferring hard-object feeding in the fossil record. Yet, inferring hard-object feeding from chipping frequencies is complicated by factors such as dental wear, age, and sex that might also affect them. Using dental remains of rhesus macaques ( Macaca mulatta ) from Cayo Santiago, Puerto Rico, we investigated whether these factors covaried with molar chipping frequencies. We hypothesized that dental wear, because it has a direct relationship to chip formation, would be a stronger predictor of chipping frequencies than age. We also hypothesized that if a sex difference were found, males would have higher frequencies of chipping than females, which is the most common sex difference in chipping found in humans. Samples consisted of 36–38 molars from females and 60–63 molars from males per molar type. Dental wear was measured and chips were identified on consistently oriented occlusal surface photographs. We performed a logistic General Linear Mixed Model (GLMM) of chipping with data on wear and chipping for the six different molar types treated as repeated measures for individuals. The GLMM revealed statistically significant effects for wear and sex, but not for age, on chipping. Our results suggest that wear has a greater effect on chipping frequencies than age, and that sex, at least in this sample, can also affect chipping frequencies. Sex differences in chipping frequencies of the magnitude found here could potentially obscure dietary signals inferred from chipping in studies of fossil primates. These findings suggest that analyzing chipping frequencies with respect to wear and sex could help improve the accuracy of dietary reconstruction of fossil primate diets based on chipping.